The efficacy of the attack and block in game phases on male FIVB and CEV beach volleyball - Giatsis, G.; Lopez Martinez, A. B.; Gea Garcia, G. M. (Journal of Human Sport & Exercise, 2015)
The aim of this study was to investigate the efficacy and differences of the attack, block, and reception in side out and counter-attack phases during beach volleyball games. A total of 80 games of FIVB World Tour and European Championships were analyzed. The technical skills analyzed were the type and efficacy of the attack, the type of block, and the efficacy of reception. The sample included 13.939 rallies, including attack (n=7.090), block (n=7.090), and serve reception (n=5.161). Descriptive statistics were applied in order to obtain frequencies and percentages. Inferential statistics were calculated (p<.05) through chi square tests. The results showed that the spikes were more frequent values than shots at both side out and counter-attack phases. Attack errors and kills were the more frequent values in both phases. Perfect receptions showed a kill percentage similar to situations when the reception was limited. It was concluded that players should make fewer errors when spiking, and coaches should pay more attention to fake blocks during both side out and counter-attack phases.